Penerapan Metode Pengajaran Klasik dalam Pendidikan Islam Modern - Zainuri, Siti Machmudah; Sirojudin, Rumbang; Lazzavietamsi, Fandy Apden; Wasehudin, Wasehudin; Lugowi, Rifyal Ahmad (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
This study examines the relevance and application of classical Islamic education methods in the modern education system. Educational methods that have developed since the time of the Prophet Muhammad SAW, Khulafaurrasyidin, Banu Umayyah, and Banu Abbasiyah have holistic characteristics that include cognitive, affective, and psychomotor aspects. Methods such as dialogue and question and answer, lectures, stories, as well as demonstrations and hands-on practice have proven to be effective in shaping the character and skills of students. With a qualitative approach based on literature study, this study analyzes the integration of classical methods in modern learning concepts such as deep learning and constructivist pedagogy. The results of the study show that the classical method remains relevant and can be applied in the contemporary Islamic education system to increase deep understanding, critical thinking, and strengthen the character of students. In addition, the classical method also encourages experiential learning, collaboration, and active involvement of students in the educational process. Therefore, the integration of classical Islamic educational values in the modern curriculum is an important strategy in building a generation that is knowledgeable, has strong character, and is ready to face global challenges. Thus, the adaptation of classical methods in modern Islamic education is expected to create a more effective, innovative, and sustainable learning system.